Bioactives and functional food ingredients with promising potential for the management of cerebral and myocardial ischemia: a comprehensive mechanistic review. Issue 13 (14th June 2022) - Zahran, Eman Maher; Sayed, Ahmed M.; Alaaeldin, Rania; Elrehany, Mahmoud A.; Khattab, Amira R.; Abdelmohsen, Usama Ramadan
Abstract : Ischemia is a deadly disease with complex pathophysiology and has a limited number of drugs. A compilation of the mechanistic studies of food bioactives with multimodal actions and higher safety has been provided in this review. Abstract : Ischemia is a deadly disease featured by restricted perfusion to different organs in the body. An increase in the accumulation of reactive oxygen species and cell debris is the driving force for inducing many oxidative, inflammatory and apoptotic signaling pathways. However, the number of therapeutics existing for ischemic stroke patients is limited and there is insufficient data on their efficiency, which warrants the search for novel therapeutic candidates from natural sources. Herein, a comprehensive survey was done on the reported functional food bioactives ( ca. 152 compounds) to manage or protect against health consequences of myocardial and cerebral ischemia. Furthermore, we reviewed the reported mechanistic studies for their anti-ischemic potential. Subsequently, network pharmacology- and in silico -based studies were conducted using the reported myocardial and cerebral ischemia-relevant molecular targets to study their complex interactions and highlight key targets in disease pathogenesis. Subsequently, the most prominent 20 compounds in the literature were used in a comprehensive in silico -based analysis (inverse docking, Δ G calculation and molecular dynamics simulation) to determine other potential targets for these compounds and their probable interactions with different signaling pathways relevant to this disease. Many functional food bioactives, belonging to different chemical classes, i.e., flavonoids, saponins, phenolics, alkaloids, iridoids and carotenoids, were proven to exhibit multifactorial effects in targeting the complex pathophysiology of ischemic conditions. These merits make them valuable therapeutic agents that can outperform the conventional drugs, and hence they can be utilized as add-ons to the conventional therapy for the management of different ischemic conditions; however, their rigorous clinical assessment is necessary.